Mirador - Uma Ferramenta para Monitoramento e Gerenciamento de Multicomputadores - Araújo, Luís Augusto C. de; Trindade Júnior, Onofre (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
Technological advances in computer memory, communication networks and central processing units have made the use of computer networks, as parallel machines, a cost-effective, high-performance solution. To the user's point of view, it is very important the availability of tools for the monitoring and management of this class of system. The entire machine must look as a single system and not a collection of independent machines. This paper presents the Mirador: a graphic tool for the monitoring and management of multicomputers, including those ones based on local area network technology. The Mirador can be used from any machine in the network running a WWW browser, with support to the Java language. The tool does not depend on any specific computer platform. Several tasks can be performed with the use of the Mirador, including: task removal, node interaction, monitoring of memory occupation and processor load and detection of hardware malfunctions.